2012
DOI: 10.3389/fcimb.2012.00101
|View full text |Cite
|
Sign up to set email alerts
|

Particle-size dependent effects in the Balb/c murine model of inhalational melioidosis

Abstract: Deposition of Burkholderia pseudomallei within either the lungs or nasal passages of the Balb/c murine model resulted in different infection kinetics. The infection resulting from the inhalation of B. pseudomallei within a 12 μm particle aerosol was prolonged compared to a 1 μm particle aerosol with a mean time-to-death (MTD) of 174.7 ± 14.9 h and 73.8 ± 11.3 h, respectively. Inhalation of B. pseudomallei within 1 μm or 12 μm particle aerosols resulted in a median lethal dose (MLD) of 4 and 12 cfu, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…The BALB/c mouse, a model that reflects the clinical course of human acute melioidosis [3], [4], [6], [10], [19], [20], was used to obtain reproducible manifestations of neurological melioidosis that includes aspects of leptomeningitis, meningoencephalitis, encephalomyelitis and brain abscesses secondary to remote infected foci. After adoptive transfer of infected cells, the initial meningeal foci were localized in the regions surrounding cerebral superior sagittal sinus because, on day 2 post-transfer, macroscopic brain abscesses, encephalomyelitis, brain stem encephalitis and even neutrophil infiltration in another meningeal place were not found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BALB/c mouse, a model that reflects the clinical course of human acute melioidosis [3], [4], [6], [10], [19], [20], was used to obtain reproducible manifestations of neurological melioidosis that includes aspects of leptomeningitis, meningoencephalitis, encephalomyelitis and brain abscesses secondary to remote infected foci. After adoptive transfer of infected cells, the initial meningeal foci were localized in the regions surrounding cerebral superior sagittal sinus because, on day 2 post-transfer, macroscopic brain abscesses, encephalomyelitis, brain stem encephalitis and even neutrophil infiltration in another meningeal place were not found.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the bacteria colonizing the lungs, lymph nodes and brain disseminate locally from infected foci [7], [20]. The induction of interferon-γ (IFN-γ) and the activation of phagocytic cells are essential for the early control of B. pseudomallei in mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparative studies in animal models have been conducted using experimental systems that can differentially deposit pathogens in the LRT and URT within small or large particle aerosols 69 - 77 . The general theme running through studies investigating the effects of aerosol particle size on infectivity is that greater numbers of pathogens need to deposit in the URT to produce lethal infection compared with the LRT (Tables 3 and 4).…”
Section: Pathogenesis As a Function Of Particle Size In Animal Modelsmentioning
confidence: 99%
“…Thus, greater lung pathology occurred after the inhalation of the 1-μm aerosolized particles. 41 These findings have important implications for the risk of inhalational melioidosis in endemic countries during the monsoon season, which facilitates the aerosol transmission of melioidosis infections and leads to pneumonic infections.…”
Section: Discussionmentioning
confidence: 95%
“…The median length (0.606 μm) and median width (0.460 μm) of B. pseudomallei cells in the endemic soil microcosm demonstrated in this study (Table 1) suggest the possibility that this pathogen could be retained in the lungs and therefore highlights the risk of transmission of melioidosis by inhalation, as was previously suggested by Sagripanti and others 38 and Thomas and others. 41 The Balb/c murine model of inhalational melioidosis exhibited a shorter mean time to death when 1-μm B. pseudomallei aerosol particles were inhaled compared with when 12-μm particles were inhaled, as well as a lower median lethal dose of 4 and 12 CFU, respectively. Thus, greater lung pathology occurred after the inhalation of the 1-μm aerosolized particles.…”
Section: Discussionmentioning
confidence: 95%